Pendampingan Pelatihan Halal Preneur melalui Sertifikasi Halal bagi Pelaku UMKM di Desa Selogiri, Kecamatann Karanggayam, Kabupaten Kebumen - Ash-Shiddiqy, Muhammad; Pratama Putra, Bayu; Nada Fauziah, Syarifa; Okta Marcella, Nafa; Ichlasul Amal, Muhammad (Madani: Jurnal Pengabdian Ilmiah, 2024)
The purpose of this service activity is to provide understanding and assistance about the importance of halal certification for Micro, Small and Medium Enterprises (MSMEs) actors, especially in Selogiri Village, Karanggayam District, Kebumen Regency by providing an understanding of the influence of the halal label in the form of product certification, building experience regarding steps -Steps for submitting halal certification to the Ministry of Religion through the application. By adding insight and experience, it can increase productivity and competitiveness for MSME actors in Selogiri Village, Karanggayam District, Kebumen Regency. In addition, it is also able to expand the scope of sales for the environment around MSME activists. Counseling activities are carried out through the stages of outreach to business actors to assistance in registering halal product guarantee certification online for 15 MSME actors engaged in the culinary field of small and medium scale businesses. With the assistance of this halal certification process, all problems regarding how to arrange halal certificates which are considered difficult can be resolved and become an example for other MSMEs in the Selogiri Village, Karanggayam District, Kebumen Regency.